The Grammatical Category of Mood in School Books of Greek Primary Education: Description, Evaluation and Teaching Suggestions - Κουρέτση, Δέσποινα (Education Sciences, 2022)
This paper aims to describe the grammatical category of Mood as it is presented by modern linguistic studies, the school grammar and the school books of Greek language in Primary Education. The paper presents the most important outcomes of the science of linguistics about Mood, focusing on its morphological characteristics, without expanding on the semantic traits, which compose the notion of Modality. In addition, the paper describes the presence of Mood in grammar book and school books of Primary school and it tries to criticize it. Finally, the present paper proposes ideas for the teaching approach of Mood in Primary school, according to the outcomes of modern linguistic studies.